2014
DOI: 10.1371/journal.pone.0105931
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Brain Changes beyond Visual System in Patients with Advanced Glaucoma

Abstract: In order to test the hypothesis that in primary open angle glaucoma (POAG), an important cause of irreversible blindness, a spreading of neurodegeneration occurs through the brain, we performed multimodal MRI and subsequent whole-brain explorative voxelwise analyses in 13 advanced POAG patients and 12 age-matched normal controls (NC). Altered integrity (decreased fractional anisotropy or increased diffusivities) of white matter (WM) tracts was found not only along the visual pathway of POAG but also in nonvisu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
113
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 102 publications
(128 citation statements)
references
References 48 publications
14
113
1
Order By: Relevance
“…Cortical replasticity and cross-model plasticity have been widely observed in the brain of glaucoma patients. 30,33,34 Consistent with our present results, Williams et al 33 previously reported that patients with glaucoma may have volumetric gains in some structures early in disease, but that brain volumes decrease toward and in some cases below control volumes as the disease progresses. Li et al 30 reported significantly decreased GMV in the lingual gyrus, calcarine gyrus, postcentral gyrus, superior frontal gyrus, inferior frontal gyrus, and rolandic operculum of both sides, the right inferior occipital gyrus, left paracentral lobule, right supramarginal gyrus, and right cuneus in POAG patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Cortical replasticity and cross-model plasticity have been widely observed in the brain of glaucoma patients. 30,33,34 Consistent with our present results, Williams et al 33 previously reported that patients with glaucoma may have volumetric gains in some structures early in disease, but that brain volumes decrease toward and in some cases below control volumes as the disease progresses. Li et al 30 reported significantly decreased GMV in the lingual gyrus, calcarine gyrus, postcentral gyrus, superior frontal gyrus, inferior frontal gyrus, and rolandic operculum of both sides, the right inferior occipital gyrus, left paracentral lobule, right supramarginal gyrus, and right cuneus in POAG patients.…”
Section: Discussionsupporting
confidence: 92%
“…Altered integrity of WM tracts and brain atrophy was detected in both visual cortex and other distant nonvisual regions. 34 Differences between studies could be due to heterogeneity of patient groups or the different image processing and averaging techniques employed. The data are, however, consistent with the occurrence of cortical replasticity in the brain of patients affected by glaucoma, a phenomenon that merits further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…19 Volume changes beyond the visual system in glaucoma patients also have been reported in several studies but with inconsistent results. For instance, Frezzotti et al 21 reported that POAG patients had brain atrophy in some gray matter regions and the visual cortex. By contrast, Williams et al 22 found five cerebral structures larger in the glaucoma group than in the control group.…”
Section: Optic Radiations Microstructural Changes In Glaucomamentioning
confidence: 99%
“…[16][17][18] In addition, epidemiologic studies also have suggested that glaucoma might be associated with other neurodegenerative disorders, in particular Alzheimer's disease, 19,20 and a few studies have found a reduced volume of brain structures beyond the visual pathways, particularly in the hippocampus, which is well known to be affected in Alzheimer's disease. 14,21,22 These data have nevertheless been collected in patients with longstanding disease. Whether subtle alterations suggestive of associated neurodegenerative disease can be captured from the early stage of glaucoma, before atrophy, is unknown.…”
mentioning
confidence: 99%
“…In this regard, a recent study using multimodal MRI and whole-brain explorative voxelwise analyses, showed the occurrence, in patients with advanced glaucoma, of structural and functional changes not limited to the white matter tracts of the visual pathway, but also extended to nonvisual areas of the central nervous system, such as superior longitudinal fascicle, anterior thalamic radiations, corticospinal tract, middle cerebellar peduncle, frontoparietal cortex, hippocampus and cerebellar cortex (Frezzotti et al, 2014).…”
Section: Introductionmentioning
confidence: 99%